Pengaruh Lingkungan dan Fasilitas Kerja Pada Kinerja Karyawan Pada PT.KSI 2 POM I di Kabupaten Seruyan Kalimantan Tengah - Habiburahman Habiburahman; Nurhayati Nurhayati; Muhammad Zainuddin; Vicky Satria Rahmadhan Lihu (eCo-Buss, 2025)
PT KSI POM 1, located in Seruyan Regency, Central Kalimantan, is a subsidiary of the Wilmar Group and plays a significant role in the palm oil industry. This study aims to examine the influence of the work environment and work facilities on employee performance. A quantitative approach was employed using an explanatory survey method. Data were collected through questionnaires distributed to 93 employees and analyzed using SPSS version 27. The results indicate that both the work environment and work facilities have a significant effect on employee performance. The work environment has a positive influence, with a t-value of 3.330 and a significance level of less than 0.05. Meanwhile, work facilities show a stronger impact with a regression coefficient of 1.397. Simultaneously, these two variables explain 80.7% of the variation in employee performance, as indicated by the Adjusted R² value of 0.807. These findings suggest that enhancing workplace comfort and ensuring the availability of adequate facilities can improve employee productivity. Therefore, it is recommended that companies provide proper lighting, maintain optimal temperature conditions, and regularly maintain workplace infrastructure to support employee well-being and efficiency.